FUNGSIONALISASI SANKSI PIDANA DALAM MENANGGULANGI TINDAK PIDANA DI BIDANG PERLINDUNGAN KONSUMEN UNTUK MELINDUNGI KONSUMEN DARI BAHAYA KOSMETIK TIDAK BERLABEL - Ferdian Soni; Ade Adhari (Jurnal Hukum Adigama, 2021)
Currently, there are many cosmetic products circulating in the market that are not labeled without knowing the composition contained in them, so that it endangers consumers. The problems faced in this study are how effective the use of criminal sanctions in providing protection to consumers from unlabeled cosmetic products is and how to functionalize criminal sanctions in providing protection to consumers from unlabeled cosmetic products. The research method used in this research is normative juridical law research. The results of the study indicate that Law Number 8 of 1999 concerning Consumer Protection has basically provided legal protection to consumers. Criminal sanctions against perpetrators who produce or distribute unlabeled cosmetics have been clearly regulated in several laws and regulations including the Health Law, UUPK, PP Number 72 of 1998 and Perka BPOM No. HK.03.1.23.04.11.03724 of 2011 concerning Cosmetics Importation Control. In terms of being functional related to criminal sanctions in providing protection to consumers from unlabeled cosmetic products, it is by increasing public legal awareness to report on unlabeled cosmetics, conducting supervision of unlabeled cosmetics in circulation to find out who the manufacturer is and report it to the police. (c) BPOM and YLKI cooperate with law enforcement or cooperate with various parties to prevent the circulation of unlabeled cosmetics and hold a communication forum to bring together cosmetic industry producers and BPOM.